2017
DOI: 10.1186/s12882-017-0521-x
|View full text |Cite
|
Sign up to set email alerts
|

Kidney disease in Uganda: a community based study

Abstract: BackgroundChronic kidney disease (CKD) is a major cause of morbidity and mortality in Sub-Saharan Africa (SSA). The majority of studies on CKD in SSA have been conducted among HIV-infected populations and mainly from large health facilities. We determined the prevalence of CKD and its predictors among populations in communities in central Uganda.MethodsA cross-sectional study was conducted in Wakiso district using multi-stage sampling. Data was collected on age, sex, socio-economic status, history of alcohol i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
49
2
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 32 publications
9
49
2
9
Order By: Relevance
“…Although comparing available studies is difficult due to differences in CKD definition, our results are consistent with two other community-based studies from East Africa, one from central Uganda [43], and another from northern Tanzania [44]. These two studies yielded a similar prevalence of CKD (7-10%), which was also predominantly driven by proteinuria [43,44]. In West and Central Africa, community-based CKD prevalence estimates have ranged from 6-19% [45][46][47][48][49], with highest prevalence reported in Southwestern Nigeria [49].…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…Although comparing available studies is difficult due to differences in CKD definition, our results are consistent with two other community-based studies from East Africa, one from central Uganda [43], and another from northern Tanzania [44]. These two studies yielded a similar prevalence of CKD (7-10%), which was also predominantly driven by proteinuria [43,44]. In West and Central Africa, community-based CKD prevalence estimates have ranged from 6-19% [45][46][47][48][49], with highest prevalence reported in Southwestern Nigeria [49].…”
Section: Plos Onesupporting
confidence: 90%
“…Although comparing available studies is difficult due to differences in CKD definition, our results are consistent with two other community-based studies from East Africa, one from central Uganda [43], and another from northern Tanzania [44]. These two studies yielded a similar prevalence of CKD (7-10%), which was also predominantly driven by proteinuria [43,44].…”
Section: Plos Onesupporting
confidence: 87%
“…Kaze et al [50] reported history of diabetes mellitus as a strong associated factor to CKD which was convergent to the ndings of Bahrey et al [51]. Female sex was also an associated factor of CKD and this was comparable to ndings in a study in Uganda [55]. Although hypertension and diabetes mellitus were notable associated factors, these were also identi ed as main etiological factors along with chronic glomerulonephritis and HIV.…”
Section: Discussionsupporting
confidence: 67%
“…Zhang and Rothenbacher 12 in a review of population-based studies on the prevalence of CKD observed that several studies had higher prevalence of CKD in females. Kalyesubula et al 29 in a community-based study on kidney disease in Uganda also recorded a higher prevalence of CKD in the female gender. The fact that men have more muscle mass than women, and the differences in hormone metabolism and glomerular structure are assumed to play a role in the differences in prevalence of CKD observed between male and female gender.…”
Section: Discussionmentioning
confidence: 88%